TEMOBIC: Phase II Trial of Neoadjuvant Chemotherapy for Unresectable Anaplastic Gliomas: An ANOCEF Study. (20th April 2021) - Tabouret, Emeline; Fabbro, Michel; Autran, Didier; Hoang-Xuan, Khe; Taillandier, Luc; Ducray, François; Barrie, Maryline; Sanson, Marc; Kerr, Christine; Cartalat-Carel, Stephanie; Loundou, Anderson; Guillevin, Remy; et al.
Abstract : Lessons Learned : Treatment with temozolomide and BCNU was associated with substantial response and survival rates for patients with unresectable anaplastic glioma, suggesting potential therapeutic alternative for these patients. The optimal treatment for unresectable large anaplastic gliomas remains debated. Background: The optimal treatment for unresectable large anaplastic gliomas remains debated. Methods: Adult patients with histologically proven unresectable anaplastic oligodendroglioma or mixed gliomas (World Health Organization [WHO] 2007) were eligible. Treatment consisted of BCNU (150 mg/m 2 ) and temozolomide (110 mg/m 2 for 5 days) every 6 weeks for six cycles before radiotherapy. Results: Between December 2005 and December 2009, 55 patients (median age of 53.1 years; range, 20.5–70.2) were included. Forty percent of patients presented with wild-type IDH1 gliomas, and 30% presented with methylated MGMT promoter. Median progression-free survival (PFS), centralized PFS, and overall survival (OS) were 16.6 (95% confidence interval [CI], 12.8–20.3), 15.4 (95% CI, 10.0–20.8), and 25.4 (95% CI, 17.5–33.2) months, respectively. Complete and partial responses under chemotherapy were observed for 28.3% and 17% of patients, respectively. Radiotherapy completion was achieved for 75% of patients. Preservation of functional status and self-care capability (Karnofsky performance status [KPS] ≥70) were preserved until disease progression for 69% of patients. Grade ≥ 3 toxicities were reported for 52% of patients, and three deaths were related to treatment. By multivariate analyses including age and KPS, IDH mutation was associated with better prognostic for both PFS and OS, whereas MGMT promoter methylation was associated with better OS. Conclusion: The association of BCNU and temozolomide upfront is active for patients with unresectable anaplastic gliomas, but toxicity limits its use.